(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SUMARIO: 1. Introducción- 2. La problemática de las identidades – 3. El diálogo interreligioso como instrumento para la consecución de la convivencia pacífica y su promoción por el Estado -4. Diálogo interreligioso y gobernanza ciudadana. Interreligious dialogue and citizen governance ABSTRACT: The 21st century has been characterized by the emergence of identity issues. The invocation of identity in a globalized world is on the agenda of all research centers and has generated a huge intellectual and political debate. Many of the conflicts that plague the contemporary world are based on identity. Exclusionary identitarianism, whether of a religious, ethnic or nationalist nature, has taken root in many societies. They are, as the writer Amin Maalouf called them, the "killer identities", exclusionary identities based on two fundamental concepts: the conception of an identity as unique, all-embracing of the individual, and the thesis of the scapegoat. The fight against these initiatives is complex and requires different instruments. One of these instruments, in the case of radicalized religious identities, could be the promotion by the public authorities of interreligious dialogue. These initiatives would be inserted in the new concept of governance and Open Government, which encourages citizen participation in the development of public policies. The current research formulates a proposal for the application of interreligious dialogue at the municipal level as a mechanism to combat religious radicalization and exclusionary identitarianism in the search for more plural and peaceful societies.